INOVASI BOLU RAMPAH KHAS MAKASSAR DENGAN PEMANFAATAN TIGA JENIS SARI KURMA SEBAGAI PEMANIS ALAMI - Hidayat Dwi Putra; Riska Veronika; Anggun Sari Sasmita (HOME : Hospitality and Gastronomy Research Journal, 2026)
The growing public awareness of healthy lifestyles highlights the need for innovation in traditional foods so that they remain relevant and nutritionally beneficial. Bolu Rampah, a traditional spiced cake from Makassar, is typically sweetened with palm sugar. Using date extract as a natural sweetener offers the potential to create a healthier product without losing its cultural identity. This study aims to describe the production process of Bolu Rampah with palm sugar substituted by three types of date extract—Sukari, Khalas, and Lulu—and to evaluate consumer acceptance of the resulting products. A quantitative approach was employed using a hedonic test with 63 consumer panellists selected through accidental sampling at Pasar Cidu’, Makassar. Panellists used a six-point scale to evaluate five sensory attributes—texture, taste, colour, aroma, and overall appearance. The results showed that Khalas date extract received the highest scores for texture (5.34), colour (5.32), and aroma (5.39), while Lulu date extract was preferred for taste (5.27) and overall appearance (5.52). Sukari date extract consistently obtained the lowest scores across all attributes, though within the “like” category. Therefore, date extracts, particularly Khalas and Lulu, can be recommended as natural sweeteners in innovative Bolu Rampah. This study emphasises the importance of innovating traditional foods with natural ingredients and opens opportunities for further research on shelf life, nutritional analysis, and market potential to support commercial development.